The Role of Leadership and Integrity on Teacher Performance - Verawati Wote, Alice Yeni; Sero, Wiwin Priscilla (International Journal of Elementary Education, 2021)
The purpose of this research is to know whether the influence of headmaster's leadership and integrity toward teachers' performance in the Sahu district of West Halmahera or not. The data population is all elementary school teachers of Sahu District of West Halmahera represented by 67 teachers as data samples. The quantitative Descriptive Approach is used in this research with the Double Regression data analysis technique. Results of the research show that: (1) Headmaster Leadership gives a positive and significant influence on elementary school teachers' performance in Sahu district of West Halmahera; (2) Integrity gives positive and significant influence on elementary schools teachers' performance in Sahu district of West Halmahera; (3) Headmaster Leadership and Integrity gives a positive and significant influence on elementary school teachers' performance in Sahu district of West Halmahera.